Change detection as support for monitoring the dynamic of land around reservoir - Rodrigues, Thanan Walesza Pequeno [UNESP]; Guimarães, Ulisses Silva [UNESP]; Galo, Maria de Lourdes Bueno Trindade [UNESP] (Ieee, 2014)
The change detection technique was used in this study to provide preliminary information on the dynamics of land cover in the region over the western basin of the Tiete River. This area is characterized by sequence of reservoirs and intense agricultural activity, triggering series negative effects. One of the impacts is contamination and proliferation of aquatic organisms in these aquatics environments, increased by release of nutrients from human activities. This work was possible to observe a large switching classes and secondary vegetation bare land, probably related to agricultural activity.
Keywords: Land cover; Remote sensing; Reservoir; Change detection